11-Hydroxyeicosatetraenoics induces cellular hypertrophy in an enantioselective manner - Helal, Sara A.; El-Sherbeni, Ahmed A.; El-Kadi, Ayman O. S. (Frontiers in Pharmacology, 2024)
Background: R/S enantiomers of 11-hydroxyeicosatertraenoic acid (11-HETE) are formed from arachidonic acid by enzymatic and non-enzymatic pathways. 11-HETE is predominately formed by the cytochrome P450 1B1 (CYP1B1). The role of CYP1B1 in the development of cardiovascular diseases is well established.Objectives: This study aimed to assess the cellular hypertrophic effect of 11-HETE enantiomers in human RL-14 cardiomyocyte cell line and examine their association with CYP1B1 levels.Methods: Human fetal ventricular cardiomyocyte, RL-14 cells, were treated with 20 µM (R) or (S) 11-HETE for 24 h. Thereafter, cellular hypertrophic markers and cell size were then determined using real-time polymerase chain reaction (RT-PCR) and phase-contrast imaging, respectively. The mRNA and protein levels of selected CYPs were determined using RT-PCR and Western blot, respectively. In addition, we examined the effect of (R) and (S) 11-HETE on CYP1B1 catalytic activity using human recombinant CYP1B1 and human liver microsomes.Results: Both (R) and (S) 11-HETE induced cellular hypertrophic markers and cell surface area in RL-14 cells. Both enantiomers significantly upregulated CYP1B1, CYP1A1, CYP4F2, and CYP4A11 at the mRNA and protein levels, however, the effect of the S-enantiomer was more pronounced. Furthermore, 11(S)-HETE increased the mRNA and protein levels of CYP2J and CYP4F2, whereas 11(R)-HETE increased only CYP4F2. Only 11(S)-HETE significantly increased the catalytic activity of CYP1B1 in recombinant human CYP1B1, suggesting allosteric activation in an enantioselective manner.Our study provides the first evidence that 11-HETE can induce cellular hypertrophy in RL-14 cells via the increase in CYP1B1 mRNA, protein, and activity.